PERAN LEMBAGA KEUANGAN TERHADAP PERTUMBUHAN USAHA MIKRO KECIL DAN MENENGAH (Studi Kasus Di Kota Yogyakarta) - Lila Retnani Utami; V. Wiratna Sujarweni (Pusat Penelitian dan Pengabdian Masyarakat Politeknik Harapan Bersama, 2020)
The purpose of this study is to examine the role of financial institutions in the growth of small and medium-sized businesses in the city of Yogyakarta. UMKM has an important role in the economic growth of developing countries.This study looks at the role of financial institutions in terms of the simplicity of the criteria, the duration of the loan, the size of the loan, and the cost of the loan.The population of this research is the SMEs in Yogyakarta City, using incidental sampling. The data used is the data of the past 1 year. This research is a quantitative study using multiple regression analysis tools.The results obtained have a positive effect on Loan Size, Loan Costs, Loan Duration, Simplicity of criteria on MSME growth in Yogyakarta City.